Naloxone prescriptions among patients with a substance use disorder and a positive fentanyl urine drug screen presenting to the emergency department - Shawkut Amaan Ali; Jasmine Shell; Raymond Harris; Marshall Bedder (BMC, 2023)
Abstract Background Over 109,000 people in the USA died from a drug overdose in 2022. More alarming is the amount of drug overdose deaths involving synthetic opioids other than methadone (SOOM), primarily fentanyl. From 2015 to 2020, the number of drug overdose deaths from SOOM increased 5.9-fold. SOOM are commonly being found in many other drugs without the user's knowledge. Given the alarming number of overdose deaths from illicit drugs with SOOM, naloxone should be prescribed for all persons using illicit drugs regardless of if they knowingly use opioids. How often providers prescribe naloxone for these patients remains unknown. The aim of this study is to determine the rate of naloxone prescriptions given to patients with any substance use disorder, including when the patient has a urine drug screen positive for fentanyl. Secondary aims include determining what patient factors are associated with receiving a naloxone prescription. Methods The design was a single-center retrospective cohort study on patients that presented to the Augusta University Medical Center emergency department between 2019 through 2021 and had an ICD-10 diagnosis of a substance use disorder. Analyses were conducted by logistic regression and t-test or Welch's t-test. Results A total of 10,510 emergency department visits were by 6787 patients. Naloxone was prescribed in 16.3% of visits with an opioid-related discharge diagnosis and 8.4% of visits with a non-opioid substance use-related discharge diagnosis and a urine drug screen positive for fentanyl. Patients with a fentanyl positive urine drug screen had higher odds of receiving a naloxone prescription (aOR 5.80, 95% CI 2.76-12.20, p < 0.001). Patients with a psychiatric diagnosis had lower odds of being prescribed naloxone (aOR 0.51, p = 0.03). Patients who received naloxone had a lower number of visits (mean 1.23 vs. 1.55, p < 0.001). Patients with a urine drug screen positive for cocaine had higher odds of frequent visits (aOR 3.07, p = 0.01). Conclusions Findings should remind providers to prescribe naloxone to all patients with a substance use disorder, especially those with a positive fentanyl urine drug screen or a co-occurring psychiatric condition. Results also show that cocaine use continues to increase healthcare utilization.